Mechanical recoverability and damage process of ionic‐covalent PAAm‐alginate hybrid hydrogels. Issue 1 (14th September 2015) - Xin, Hai; Brown, Hugh R.; Naficy, Sina; Spinks, Geoffrey M.
ABSTRACT: Hydrogels consisting of interpenetrating networks of ionically and covalently crosslinked polymers showed high toughness and mechanical recoverability as a result of the dissociation and re‐formation of ionic crosslinks. The present investigation aimed to provide a quantitative study on the mechanical recoverability and damage process of an example hybrid gel of calcium crosslinked alginate and covalently crosslinked polyacrylamide. Three series of load/unload tests were performed sequentially with the mechanical properties of the gel fully retrieved between the 2nd and 3rd load/unload series while only the partial recovery of mechanical properties was evident from the 1st to 2nd series. The load/unload curves in the three series were modeled by existing mechanical models, and the fitted model parameters clearly demonstrate a damage process for the hybrid gel. When a hybrid gel was deformed above its historic maximum strain, the shortest alginate chains were fully‐stretched, pulling apart the weak ionic crosslinks and dissipating fracture energy. Consequently, the strand density of the intact gel network was reduced and the contour length of the remaining next‐shortest load‐bearing alginate chains became longer. A log‐normal distribution was used to describe the probability distribution for the strand fracture and also to describe the strand length distribution of the ionic network. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 53–63 Abstract : Tough hybrid hydrogels composed of an ionically crosslinked network interpenetrated with a covalent network show considerable irreversible damage in the ionically crosslinked network during initial tensile loading. Subsequent load/unload cycles show almost full recoverability of the loading‐induced network damage. Mechanical models are here used to quantify the damage and recovery processes occurring during the loading and unloading of hybrid hydrogels.